A Novel Missense Mutation of DKC1 In Dyskeratosis Congenita With Pulmonary Fibrosis - Hisata, Shu; Sakaguchi, H.; Kanegane, H.; Hidaka, T.; Ichinose, M.; Kojima, S.; Nukiwa, T.; Ebina, M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Dyskeratosiscongenita (DC) is a rare inherited multisystem disorder causedby mutations in seven genes involved in telomere biology, with approximately 20% of cases having pulmonarycomplications. DKC1 mutations exhibita severe disease phenotype of DC that develops in early childhood. Here, wereport a unique case of DC with pulmonaryfibrosis diagnosed at the ageof 46. A novel missense mutation(p.Arg65Lys) of DKC1 was detected, andpredicted to show a weak mutagenic effect. In spite of the steroid andimmunosuppressive treatment, he died of an acute exacerbation seven monthsafter the initial visit. This casesuggests that mutation subtypes can cause heterogeneity in DC and pulmonaryfibrosis.